2008
DOI: 10.1002/jhet.5570450652
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious nucleophilic amination of nitroquinolines by 1,1,1‐trimethylhydrazinium iodide

Abstract: 2 NH 2The amination of 3-, 5-, 6-, 7-and 8-nitroquinoline via the vicarious nucleophilic substitution of hydrogen (VNS) with 1,1,1-trimethylhydrazinium iodide (TMHI) in the presence of t-BuOK in DMSO was studied. The amination occurs regioselectively giving ortho or ortho and para isomers relative to the nitro group with a high yield (95-86%). 2-Nitroquinoline does not undergo vicarious amination but displacement of the labile nitro group by an amino group occurs and then transformation to an imine compound an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In agreement with our previous study that showed that removal of the hydroxyl group from position 8 of the 5nitroquinoline ring resulted in significantly lower catB inhibition (compound 31, Table S3, Supporting Information), 31 the 8-alkyloxy substituted nitroxoline derivatives assayed here also led to diminished activity (compounds 27− 30, Table S2, Supporting Information). Similarly, 8-amino-5nitroquinoline (32), 6-amino-5-nitroquinoline (33), 8-acetamido-5-nitroquinoline (36), and 5,7-dinitro-8-aminoquinoline (37) showed lower catB endopeptidase inhibition when compared with nitroxoline (for compounds 32, 33, 36, and 37, see Table S3, Supporting Information). On the basis of the docking experiments (not shown), we postulate that larger substituents are needed at position 8 of the 5-nitroquinoline, as they can then extend into the S1 and/or S2 subsite of the active site.…”
Section: Cathepsin B Inhibitory Activities and Enzymementioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with our previous study that showed that removal of the hydroxyl group from position 8 of the 5nitroquinoline ring resulted in significantly lower catB inhibition (compound 31, Table S3, Supporting Information), 31 the 8-alkyloxy substituted nitroxoline derivatives assayed here also led to diminished activity (compounds 27− 30, Table S2, Supporting Information). Similarly, 8-amino-5nitroquinoline (32), 6-amino-5-nitroquinoline (33), 8-acetamido-5-nitroquinoline (36), and 5,7-dinitro-8-aminoquinoline (37) showed lower catB endopeptidase inhibition when compared with nitroxoline (for compounds 32, 33, 36, and 37, see Table S3, Supporting Information). On the basis of the docking experiments (not shown), we postulate that larger substituents are needed at position 8 of the 5-nitroquinoline, as they can then extend into the S1 and/or S2 subsite of the active site.…”
Section: Cathepsin B Inhibitory Activities and Enzymementioning
confidence: 99%
“…The synthesis of 8-amino-5-nitroquinoline (32) proceeded smoothly by the previously described aromatic amination of 5nitroquinoline, using (31) 1,1,1-trimethyhydrazinium iodide (TMHI) and t-BuOK in dimethyl sulfoxide (DMSO) (Scheme 4). 36 Starting from the 8-aminoquinoline (34), the 8acetamido-5-nitroquinoline (36) was also synthesized. As a side product under these reaction conditions, we concurrently obtained the 5,7-dinitrated 8-aminoquinoline analogue 37 (Scheme 4).…”
Section: Chemistrymentioning
confidence: 99%
“…The aim of this work is to use cheaper hydroxylamine hydrochloride to replace the toxic 1,1,1-trimethylhydrazinium iodide (TMHI) [6][7][8] synthesizing LLM-116 (Scheme 1), to obtain the thermolysis kinetics of LLM-116 under static and dynamic state by means of different heating rate differential scanning calorimetry (DSC) [9][10][11][12][13], and to study the thermal decomposition mechanism by means of in situ thermolysis cell with rapid-scan Fourier transform infrared spectroscopy (thermolysis/RSFTIR) [14][15][16][17][18] and thermogravimetry-mass spectrometer (TG-MS) technology. * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…These positions of molecule 1 are characterized by increased electrophilic properties. Taking into account the absence of steric hindrances to the formation of a stable C-C bond at the C 6 position of nitroxaline, it can be assumed that this electrophilic center is the most active when interacting with nucleophiles, which is confirmed by data from the literature [4][5][6].…”
Section: Resultsmentioning
confidence: 63%
“…Reactions of nucleophilic substitution of hydrogen in 5-nitroquinolines have been described, which proceed in the orthoposition to the nitro group in interaction with nucleophiles containing a vicarious group (vicarious substitution) [4]. The reaction of amination of nitroquinolines with trimethylhydrazinium iodide occured in a solution of anhydrous DMSO in the presence of potassium tert-butylate [5]. Vicarious amination of nitroquinolones with 4-amino-1,2,4-triazole was carried out under similar conditions and occured at the C 6 atom of nitroquinolone [6].…”
Section: Introductionmentioning
confidence: 99%